Implementasi Program BTQ (Baca Tulis Al-Qur’an) di Sekolah LHS ( Lima Hari Sekolah) untuk Meningkatkan Belajar Pendidikan Agama Islam Siswa SMP Negeri 2 Doko - umi nahdiyah; Nanang Zamroji (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
Implementation of the Al-Qur'an Reading and Writing Program in LHS Schools (Five School Days) to Improve Islamic Religious Education Learning for Students of SMPN 2 Doko. The goal of this study is to learn more about how the program to read and write the Koran at SMPN 2 Doko was implemented. This qualitative research falls under the field research genre. The process of gathering data involves participant observation, documentation, and in-depth interviews. Data analysis is then carried out, beginning with data reduction, presentation, and conclusion. By extending the presence of researchers, using several sources of data, conducting peer reviews, and clarifying with informants, the veracity of the data was examined. According to the study's findings, SMPN 2 Doko's Al-Qur'an reading and writing program has been thoroughly implemented and planned with the school; it is now included in intra-school activities rather than local material. The Al-Qur'an employs an approach known as the Ottoman Method. Keywords: Implementation, Al-Qur'an Reading and Writing Program, Learning Outcomes.